NDRG1 acts as an oncogene in triple-negative breast cancer and its loss sensitizes cells to mitochondrial iron chelation - Jadhav, Sukanya B.; Vondrackova, Michaela; Potomova, Petra; Sandoval-Acuña, Cristian; Smigova, Jana; Klanicova, Kristyna; Rosel, Daniel; Brabek, Jan; Stursa, Jan; Werner, Lukas; Truksa, Jaroslav (Frontiers in Pharmacology, 2024)
Multiple studies indicate that iron chelators enhance their anti-cancer properties by inducing NDRG1, a known tumor and metastasis suppressor. However, the exact role of NDRG1 remains controversial, as newer studies have shown that NDRG1 can also act as an oncogene. Our group recently introduced mitochondrially targeted iron chelators deferoxamine (mitoDFO) and deferasirox (mitoDFX) as effective anti-cancer agents. In this study, we evaluated the ability of these modified chelators to induce NDRG1 and the role of NDRG1 in breast cancer. We demonstrated that both compounds specifically increase NDRG1 without inducing other NDRG family members. We have documented that the effect of mitochondrially targeted chelators is at least partially mediated by GSK3α/β, leading to phosphorylation of NDRG1 at Thr346 and to a lesser extent on Ser330. Loss of NDRG1 increases cell death induced by mitoDFX. Notably, MDA-MB-231 cells lacking NDRG1 exhibit reduced ECAR and grow slower than parental cells, while the opposite is true for ER+ MCF7 cells. Moreover, overexpression of full-length NDRG1 and the N-terminally truncated isoform (59112) significantly reduced sensitivity towards mitoDFX in ER+ cells. Furthermore, cells overexpressing full-length NDRG1 exhibited a significantly accelerated tumor formation, while its N-terminally truncated isoforms showed significantly impaired capacity to form tumors. Thus, overexpression of full-length NDRG1 promotes tumor growth in highly aggressive triple-negative breast cancer.